Improving frequency of urinary albumin testing in type 2 diabetes in primary care — An analysis of cross-sectional studies in Denmark - Persson, Frederik; Charles, Morten; Povlsen, Johan Vestergaard; Knudsen, Søren Tang (Primary care diabetes, 2021)
•Albuminuria and kidney function are important renal risk factors.•Urine sample collection is a challenge to ensure quality of care.•Trials with SGLT2 inhibition underscores importance of albuminuria measurement.•We assessed cross-sectional studies of the last decade in Danish primary care.•We found an improving frequency of renal risk assessment. To ensure high quality standards in chronic care of type 2 diabetes, it is paramount to ensure regular measurement of clinical risk factors. For prevention of diabetic kidney disease, testing for albuminuria and kidney function is vital. The majority of individuals with type 2 diabetes in Denmark are treated in general practice, and given the recent development of kidney-protective treatments, a renewed focus on renal risk factors is important. To assess the frequency of albuminuria and kidney function testing in general practice in Denmark and describe developments over the last decade. The proportion of patients with the recommended annual measurements of albuminuria and kidney function was the primary variable. We used data from subjects with type 2 diabetes in three cross-sectional general practice studies from 2009 to 2017. Data from 5592 individuals were available. Almost all subjects (96–99%) in the studies had annual measurement of kidney function performed. During the combined observation period there was a clear increase in the proportion of subjects that had albuminuria measured, from 57.2% to 68.0% to 82.8%. The regular assessment of renal risk factors in individuals with type 2 diabetes attending primary care in Denmark has seemingly improved over the last decade. This provides the required base for renal risk assessment and appropriate therapy selection.